Study of Serum Ferritin and Glycated Hemoglobin in Type 2 Diabetes Mellitus (Academia Journal of Medicine, 2019)
Background: Type 2 diabetes mellitus is a common metabolic disorder of multiple etiologies. Increased levels of serum ferritin have been  indicated to be associated with the etiology of the diabetic process, as well as in pathogenesis of various diabetic complications. The study aims  to understand the relationship between the serum ferritin and glycated hemoglobin in type 2 diabetes mellitus. Subjects and Methods: The  study was conducted at Medical College Hospital and Research Centre. A total of hundred cases of type 2 diabetes mellitus of the age group 30  – 70 years were taken for the study after satisfying the inclusion and exclusion criteria. Hundred healthy volunteers in the age group 30 – 70  years, sex matched during the same period was included in the study under the control group. Results: Serum ferritin level was significantly  high in cases compared to controls. There was moderate correlation between serum ferritin and glycated hemoglobin. There was significant  increase in serum ferritin levels in type 2 diabetics compared to the controls. There was a moderate correlation between serum ferritin and  glycated hemoglobin. Conclusion: This study explores the possibility of finding serum ferritin as a marker to explain the oxidative stress  process in type 2 diabetes mellitus. This valuable information would be helpful in proper medical intervention.
Keywords: Type 2 diabetes mellitus; Serum ferritin; Glycated hemoglobin